2018
DOI: 10.1177/1724600818783416
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the reference interval for serum pro-gastrin-releasing peptide in healthy adults of Chinese Han ethnicity

Abstract: We established the reference interval for serum proGRP, which was determined by ECLIA in the healthy Chinese Han population. Furthermore, our study suggests that it is necessary to establish the age-specific reference intervals for serum proGRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The reasons for these differences may be as follows: (a) different detection methods; SAA was mainly detected by immunoturbidimetry, enzyme-linked immunosorbent assay, or microsphere capture enzyme immunoassay [23][24][25] ; (b) there were some differences in population characteristics and regional characteristics, such as race, environment, and living habits. 26,27 All of the above parameters may have resulted in different results. The results of this study suggested that every laboratory should establish a SAA population reference interval that accounts for the regional population, factors in the regional environment, and detection system characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for these differences may be as follows: (a) different detection methods; SAA was mainly detected by immunoturbidimetry, enzyme-linked immunosorbent assay, or microsphere capture enzyme immunoassay [23][24][25] ; (b) there were some differences in population characteristics and regional characteristics, such as race, environment, and living habits. 26,27 All of the above parameters may have resulted in different results. The results of this study suggested that every laboratory should establish a SAA population reference interval that accounts for the regional population, factors in the regional environment, and detection system characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Ichihara et al conducted a survey of SAA reference interval showed that the upper limit of SAA reference interval was higher than that of this study for either Asian or Chinese populations. The reasons for these differences may be as follows: (a) different detection methods; SAA was mainly detected by immunoturbidimetry, enzyme‐linked immunosorbent assay, or microsphere capture enzyme immunoassay ; (b) there were some differences in population characteristics and regional characteristics, such as race, environment, and living habits . All of the above parameters may have resulted in different results.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies show a positive association between pro-GRP concentration and age; differences were statistically significant between groups of 10-year intervals in subjects younger than 70 years in the study by Zhao et al 2 The two studies followed methods that seem to be accurate, and are homogeneous regarding both the analytical platform used and the population studied. Nevertheless, there are some differences in the setting that can justify the discrepancies found; although, considering the respective confidence intervals of the RI and the intrinsic analytical variability of the method, these differences are probably not as relevant.…”
mentioning
confidence: 94%
“…This issue presents two different research articles on the establishment of reference intervals (RI) for serum progastrin releasing peptide (proGRP) measured with the same methodology on the Chinese population. 1,2 Yang et al 1 established the RI as the 95th percentile of the healthy population, finding a value <53.9 ng/L in adults aged 21-70 years and <75.7 ng/L for subjects aged >70 years, respectively, with no differences related to gender. Zhao et al 2 found values approximately 20% higher, also in this case without differences between the sexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation